2020
DOI: 10.3389/fvets.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Causes Immune Abnormalities via Massive Damage to Effect Proliferation and Differentiation of Lymphocytes in Broiler Chickens

Abstract: Broiler chickens are highly sensitive to high ambient temperatures due to their feathers, lack of skin sweat glands, and high productivity. Heat stress (HS) is a major concern for the poultry industry because it negatively affects growth as well as immune functions, which increase the potential risk of infectious disease outbreaks. Therefore, it is vital to elucidate HS's effect on the avian immune system, especially considering the global rise in average surface temperature. Our study identified a series of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 52 publications
4
85
1
2
Order By: Relevance
“…The decreased passage rate of digesta in the fermented wet feed group increases the digestion and absorption time, which in turn increases nutrient retention [ 5 ]. The availability of adequate quantities of nutrients elevated metabolic rates, thereby stimulating the production of growth hormone-releasing hormone from the hypothalamus to promote GH amplification [ 2 , 16 , 47 ]. In addition, the release of IGF-1 is induced by the enhanced expression of GH [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased passage rate of digesta in the fermented wet feed group increases the digestion and absorption time, which in turn increases nutrient retention [ 5 ]. The availability of adequate quantities of nutrients elevated metabolic rates, thereby stimulating the production of growth hormone-releasing hormone from the hypothalamus to promote GH amplification [ 2 , 16 , 47 ]. In addition, the release of IGF-1 is induced by the enhanced expression of GH [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under summer conditions, elevated ambient temperature, as an abiotic environmental factor, impairs poultry performance and evokes several physiological, immunological and behavioral changes in birds [ 1 , 2 ]. Biotic factors such as nutrition and infectious diseases can act as environmental stressors independently and often elevate the risks of abiotic factors synergistically [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress has a profound deleterious impact on broiler health and well-being. It suppresses immunity and disrupts physiological homeostasis, leading to hypersensitivity to neuroinflammation and metabolic disorders; consequently, production performance is impaired and diminished body weight, body weight gain, and increased feed conversion ratios are noted [50]. These alterations have a harmful effect on neurons and their function, causing brain ultrastructural damage and dysfunction, including mental and emotional disorders expressed at both memory and fear responsive levels [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In poultry, growing research has specifically demonstrated the negative effects of high ambient temperatures on the immune response. Heat stress also induces several immune defects in the broiler by affecting the maturation of T and B cells in lymphoid tissue [ 30 ].…”
Section: Heat Stressmentioning
confidence: 99%